Income inequality, skills and trade : evidence from Colombia during the 80s and 90s (2004)
This paper investigates the evolution of labor income inequality in Colombia in the period 1978-98. Main findings are the secular fall of the returns to intermediate skill and the increases of wages for highly educated people and for women. Such changes are associated with shifts of the skill composition of the labor force and with skill biased technical change, rather than with increased openness of the economy. The paper uses a skill supply and demand framework to arrive to these conclusions, and also a non-parametric decomposition exercise is carried out.